Preservatives in glaucoma medication. Issue 11 (4th July 2018) - Steven, David W; Alaghband, Pouya; Lim, Kin Sheng
Abstract : Preservatives continue to be in widespread use in ophthalmic medications due to the convenience they provide, regulatory requirements and the higher cost of alternatives. Benzalkonium chloride (BAK) remains the most commonly used preservative but there is a trend towards the use of preservative-free (PF) drops for glaucoma, although at a higher price. An extensive body of literature explores BAK toxicity on ocular structures in animal and laboratory studies (in vitro and in vivo). Non-randomised controlled studies have provided some supporting evidence of its toxicity in patients, especially in those with pre-existing ocular surface disease (OSD) or on multiple medications. However, there have been very few randomised controlled trials that compare the same medication with and without BAK preservative. Several of these trials have never been published in any peer reviewed journals. Notwithstanding, those that have been published, have not demonstrated any clear benefits of the BAK-free formulations. Short duration and exclusion of those with OSD are limitations of these studies. There is a lack of evidence of clinically significant harm from a small number of BAK preserved drops in patients without OSD. This means that generally more expensive PF glaucoma medications should only be recommended for those on poly pharmacy or those with OSD but are not necessarily required for all patients.